Minimally invasive plate osteosynthesis - Babst, Reto; Bavonratanavech, Suthorn; Pesantez, Rodrigo (Thieme, 2012)
This textbook offers a comprehensive view of all aspects of minimally invasive plate osteosynthesis (MIPO). The second expanded edition includes the expert knowledge of AO surgeons from all around the world. It not only provides basic concepts and the latest clinical and basic scientific research, but guides the interested surgeon through the crucial steps of MIPO application in the different anatomical regions.